Przegląd krajowych jednostek certyfikujących rolnictwo i przetwórstwo ekologiczne w świetle projektu rozporządzenia o rolnictwie ekologicznym - Szołtysek, Katarzyna; Dziuba, Szymon (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This article is a summary of the units which are present on the Polish market that certify organic agriculture through the use of organic agricultural label. However, according to the new law act it will not be applicable to signing national organic products since Jan. 1st 2009. That is so because the above mentioned act introduces new regulations as regards the matter in question. Up to this time the signs of specific units approved by the Polish Centre for Accreditation in accordance with the PN-EN 45011:2000 norm will certainly appear on our markets. It is of crucial importance that they are familiar to and identified by customers. In the light of this matter, their popularization among all the potential consumers of organic food seems justified and reasonable. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (7); 2007; nr 1185, s. 192-204